Socioeconomic Inequality in Life Expectancy: Perception and Policy Demand - Lasse J. Jessen; Sebastian Koehne; Patrick Nüß; Jens Ruhose (Center for Economic Studies and ifo Institute (CESifo), 2024)
Using survey experiments in the United States and Germany with 12,000 participants, we examine perceptions of life expectancy inequality between rich and poor people. The life expectancy of the poor is underestimated more than that of the rich, leading to exaggerated perceptions of inequality in both countries. Receiving accurate information narrows concerns about this inequality. However, the impact of information on policy demand is limited because support for policies addressing life expectancy for the poor is consistently high, regardless of varying perceptions of inequality. We conclude that there is strong and unconditional public support for health equity policies.
Keywords: C90; D71; D83; I14; I18; 330; socioeconomic inequality in life expectancy; health care; information treatment; survey experiment